تخطيط فضاءات اللعب داخل البيئة الحضرية بين التصور و الواقع - صاحبي وهيبة; نوادري فريدة (Journal of Architecture and environment of child, 2020)
Play has several areas, facilities and spaces within the urban environment that help the child to meet his basic needs related to various developmental aspects and achieve emotional balance as well as stimulating social relations to ensure his proper growth from psychological, mental, physical and sensory aspects. Despite the importance of these spaces, they didn’t take their place on the ground in the urban environment, therefore, we are trying through this research paper to focus on the necessity of providing play spaces with international standards and controls that ensure their quality and fit the child’s needs, in addition to including them in the city’s urban design due to its crucial role in maintaining the child’s health and developing his personality at all levels. Key Words: Spaces, Play, Urban Environment